Balancing Acts: Addressing Economic Inequality through Academic Freedom in Industrialization of Developing Countries - Paul, Linda; Rena, Prof. Dr. Ravinder (Contemporary Issues of Business and Management: The Proceedings of the \(10^{th}\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
In developing nations, economic inequality hinders sustainable industrialization. Academic freedom, by fostering critical thinking and creativity, is crucial for addressing this issue. It promotes human capital development, problem-solving, and innovative approaches to tackle the root causes of inequality. Academic freedom has a favourable impact on economic inequality by increasing access to education and permitting social mobility; nevertheless, its effectiveness is limited by inclusive industrial policies and strong institutional backing. An exploratory and qualitative approach was used to investigate how academic freedom, as a basis of higher education, might contribute to social equality and sustainability. The study identifies how academic freedom can improve human capital, stimulate innovation, and inform equitable policy decisions by conducting an in-depth analysis of secondary data and contemporary literature. The study adds to the conversation by illustrating that academic freedom alone is insufficient to achieve equal results; it must be accompanied by robust governance and policies that promote social inclusion. These findings have far-reaching ramifications for governments, academic institutions, civil society organizations, and international development agencies. By incorporating academic freedom into national development plans, stakeholders can promote more inclusive industrial growth and socioeconomic resilience. The study indicates that safeguarding academic freedom is critical for furthering social justice and sustainable economic growth.